The Coagulation-flocculation Process of the Liquid Waste Treatment Plant at a Diagnostic Center in Yogyakarta, Indonesia - Doddy Irawansyah; Muhammad Hanif; Sugiyanto Sugiyanto; Dikpride Despa (INSTEP Publishing Network, 2022)
The study aimed to obtain the optimum dose of Al2(SO4)3 coagulant, which would be added to the coagulation-flocculation process to redesign a liquid waste treatment plant at a diagnostic center in Yogyakarta, Indonesia. The redesign aims to reduce the content of Chemical Oxygen Demand (COD) contaminants based on Provincial Decree number 65/Y1999 which concerns the Liquid Waste Quality Standards for Health Service Activities in the Province of the Special Region of Yogyakarta. The case was studied at the diagnostic center on Dr. Soetomo street, Bausasran Village, Yogyakarta City. The research method used is quantitative, with data collection techniques in the form of primary and secondary data through survey activities on the research objects in the field. The test and analysis were carried out at the environmental laboratory in Yogyakarta. Based on the jar-test analysis, the redesign process may significantly decrease the COD pollutant from 471.94 mg/liter to 140.763 mg/ liter or 70.17%. By getting the optimum dose of the Al2(SO4)3 coagulant.